An expanded post-disaster needs assessment about the effects of Typhoon Yolanda on the University of the Philippines Tacloban College Library towards the development of a disaster management plan - Plimaco, Paul Kirby B.; Isip, Jonathan D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Cultural institutions like libraries play an important role defining a people's identity and culture. In context to a disaster, libraries help in the rebuilding of a community both culturally and economically. However, disaster planning for libraries in the Philippines have long been a challenge due to budget cuts and the lack of adequate training and programs for disaster resiliency.
It is in this light that this research looks into how the effects of Typhoon Yolanda on the UP Visayas- Tacloban College Library could inform the creation of a disaster risk reduction and management plan that could better protect the library from similar disasters in the future.
Using the Post-Disaster Needs Assessment (PDNA) for Culture by the UN System as a guide, data pertaining to the library's pre-disaster baseline, the typhoon's effects, and the library's recovery efforts was collected through interviews and archival research. An expansion to the PDNA was also introduced by incorporating a follow up on the library's efforts towards resiliency.
It was found that the magnitude of the storm severely damaged the library's primary assets thus hindering the delivery of its vital services. Even with a preparedness plan in place, the lack of an institutionalized disaster management plan compromised the library's swift and efficient recovery. Despite efforts, to introduce additional measures to protect from future disasters, there is still no formal effort in institutionalizing a disaster plan for the library.
For the UP Visayas Tacloban College Library in particular, measures to strengthen their data and asset (collection, services, human resources) management, towards disaster resiliency is recommended.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Visayas -- Tacloban College Library; Library buildings -- Safety measures; Emergency management